Ice Shelf - Ocean Interaction in the Eastern Weddell Sea, Antarctica - Hattermann, Tore (Universitetet i Tromsø, 2012)
Papers 3 and 4 are not available in Munin: 3. T. Hattermann, L. H. Smedsrud, O. A. Nøst, J. M. Lilly, and B. Galton-Fenzi: 'Modeling basal melting below the Fimbul Ice Shelf, Antarctica' (manuscript) 4. Q. Zhou, T. Hattermann and O. A. Nøst: 'Wind-driven spreading of fresh Antarctica Surface Water below ice shelves in the Eastern Weddell Sea' (manuscript) This thesis investigates the interaction of the Antarctic ice shelves along the coast of Dronning Maud Land with the ocean circulation in the Eastern Weddell Sea. A set of direct oceanic observations below the Fimbul Ice Shelf, which were acquired during three Antarctic field seasons in the austral summers 2009/10, 2010/11 and 2011/12, is a central element of the presented work. This new oceanographic dataset is complemented by a high-resolution state-of-the-art ice shelf - ocean circulation model. The results provide an estimate of the amount of basal melting at the Fimbul Ice Shelf, and revise the physical processes that determine the ocean heat fluxes over the East Antarctic continental slope. A major finding is that deep-ocean heat fluxes towards the ice are much more constrained than predicted by previous ocean models, causing substantially lower rates of basal melting than earlier suggested. The predicted basal melting is consistent with mass balance estimates from satellite data and implicates that the Fimbul Ice Shelf is currently not subject to rapid basal mass loss. Furthermore, the complex interplay of the processes within the coastal, frontal system, and their respective role in transporting heat for melting towards the ice is examined. The results emphasize the importance of oceanic eddies within the coastal circulation for controlling the inflow of Warm Deep Water into the ice shelf cavities. A realistic representation of the effect of the mesoscale eddy overturning is thus a crucial requirement in order to simulate basal melting along the Weddell Sea coast in the present and future climate. The results also imply that fresh, and solar-heated ...